KEUNGGULAN KITAB UPANISAD DALAM MENCIPTAKAN PESERTA DIDIK BERKUALITAS (Sebuah Kajian Pendidikan Kritis Agama Hindu) - Ni Made Suwarsi; I Nyoman Sueca; I Nyoman Suadnyana; I Ketut Sandika (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
There are twelve significant Upanisad scriptures. These scriptures described about God, soul and universe in an esoteric philosophical way. Furthermore, Upanisad main scriptures explicitly explained about an education system that can develop students’ intelligence holistically. Education system in Upanisad scriptures emphasized on an integrated learning aspects to build a cognitive, affective and psychomotoric behavior which involves the relationship between the teacher and the students. The excellence values of Upanisad scriptures that need to be evaluated to create an education system that can produce qualified students physically and mentally as described in the national education system. Upanisad education system should be able to be realized in Indonesia’s education system, particularly in teaching Hindu religion. Currently, Indonesia’s education system has not reached an ideal and optimal condition to produce qualified students. In Upanisad scriptures, we can say that it is a qualified system if it can create qualified students who not only have cognitive intelligence, but also spiritual intelligence in their behavior. Therefore, the education system in Upanisad scriptures emphasized on the process of experiencing rather than memorizing all theoretical formulas. The focus of this research is about the excellence values in Upanisad scriptures in creating qualified students.